ANALISIS KEMAMPUAN BERPIKIR KRITIS MATEMATIS PESERTA DIDIK KELAS XI MIPA SMA NEGERI 2 PADANG - RETNO AULIA (Departemen Matematika, 2018)
Critical thinking ability is a competency that must be trained in students because critical thinking skills are needed to compete in the 21st century. In the learning process critical thinking skills have not been implemented properly. The purpose of this study was to describe describing the level of mathematical critical thinking skills of students of class XI MIPA 5 Padang 2 High School. Data retrieval is done by observing, giving a test of mathematical critical thinking skills, then conducting interviews based on the results of tests of critical thinking skills in each group of high, medium, and low. Based on the results of data analysis, it was concluded that studentscritical thinking skills were still relatively low. Based on the results of the analysis of the data obtained it can be concluded that the students' critical thinking skills are still relatively low. There are still many students who have not been able to fulfill well every indicator of critical thinking skills that has been tested, namely interpretation, analysis, evaluation and interpretation. This is because the learning process is still dominated by the teacher. The learning process that takes place is not all material that uses the ability to think critically in solving problems. Keywords—Analysis, critical thinking skills.